The development of criminological thought: context, theory and policy - Posick, Chad (Routledge, 2018)
Science, theory, and empirical investigation -- Crime and victimization -- Pre-enlightenment theories -- Early biological theories -- Social disorganization theories -- Anomie and strain theories -- Differential association and social learning theories -- Labeling and critical criminology -- Social and self-control theories -- Deterrence and rational choice theories -- Developmental criminology -- Biosocial criminology -- Criminology in international perspective -- Theory and various crime types -- The future of criminological theory